A scoping review of frameworks evaluating digital health applications - Orla Deegan; Eoghan O Riain; Denis Martin; Mai Yoshitani; Mairead O’Donoghue; Keith Smart; Sinead McMahon; Trish O’Sullivan; Declan J O’Sullivan; Aaron Cole; Ciara Hanrahan; Catherine Blake; et al. (Digital Health)
Objectives Despite rapid technological advances, the adoption and deployment of digital health and virtual reality (VR) applications in healthcare appears to be progressing slowly. This scoping review is part of the Scale-Up4Rehab (SU4R) project, which aims to create a virtual rehabilitation clinic hosting high-quality digital health interventions. The aim of this review was to identify existing high-quality digital health evaluation frameworks, and from these, extract criteria to inform a new set of guidelines for assessing the applications that will be hosted on the SU4R platform. Methods The review followed Arksey and O’Malley's scoping review framework and was reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A search strategy that included relevant keywords encompassing the domains of interest; digital health, evaluation frameworks and digital health applications was created between January 2007 and December 2023, across seven medical and computer science databases. Data from each study were extracted by a team of four reviewers using a customized data extraction tool. Results The review included 18 frameworks from 11 countries, incorporating 775 criteria. Nine evaluation frameworks were identified from the included papers (n = 12) and a further nine frameworks from grey literature. The criteria were grouped into 19 categories, with the largest proportion of identified criteria grouped into the categories ‘Data Security and Privacy’ and ‘Validation’. Conclusion The criteria extracted from the reviewed frameworks will contribute to the creation of a comprehensive evaluation framework. This new evaluation framework will form part of the approval process for the SU4R Virtual Rehabilitation Clinic. This will facilitate a rigorous selection process for the digital health and VR applications to be hosted on the virtual clinic.